Analysis of pedestrian wayfinding under herd effect in VR fire evacuation at indoor library: gender difference considered - Li, Jianping; Liu, Chuanjin (Frontiers in Psychology, 2025)
BackgroundAs libraries are critical areas for fire safety and evacuation, there is a need to expand research on pedestrian evacuation in this scenario.MethodsWe designed an immersive virtual reality (IVE) experiment to examine the wayfinding choices made by pedestrians during a library fire under conditions of different crowd patterns represented by non-game players and differences in gender ratios. A total of 162 participants were asked to engage in an evacuation task in a randomized order across sixteen different experimental scenarios.Results(1) Under the influence of crowd patterns, pedestrians tended to follow the route chosen by the majority of the evacuating crowd. (2) Pedestrians tended to follow the group with a higher proportion of males in the evacuation. (3) When the proportion of males in the route chosen by the majority of the evacuating population is significantly smaller than the proportion of females, the pedestrian’s choice of that route is significantly lower. (4) The gender ratio significantly attenuates the influence of the herd effect on the subjects’ route decision-making.ConclusionThis experiment expands the study of pedestrian routing behavior in a fire situation and provides some empirical evidence for the further improvement of fire evacuation.